A single institutional experience in laparoscopic colorectal surgery: clinical and oncological outcomes over 10 years - Đermanović, Aleksandar; Radovanović, Zoran; Lukić, Dejan; Đurić, Mladen; Golijanin, Danica; Ranisavljević, Milan; Petrović, Nemanja (Archive of Oncology, 2021)
ABSTRACT Introduction: The development of laparoscopic colorectal surgery began in 1991. Today, laparoscopic surgery presents standard approach in the surgical treatment of malignant colon and rectal diseases. Aim: Outcomes and survival rates of laparoscopic colorectal surgery at the Oncology Institute of Vojvodina. Methods: Data were collected prospectively from 66 patients undergoing laparoscopic colorectal surgery between December 2009 and December 2019. Registered data included sex, age, surgical indication and type for the procedure, indication and reason for conversion to open surgery, operative time, performing temporary or permanent stoma, intraoperative bowel perforation , pathologic TNM grade, number of harvested lymph nodes, inclusion of positive resection margin, number of postoperative days at the hospital, postoperative complications, postoperative mortality, presence of distant metastases and survival rates. Results: The procedures performed by the laparoscopic method were right hemicolectomy in 11/66 (16.7%) patients, left hemicolectomy in 1/66 (1.5%), sigmoid colectomy in 19/66 (28.8%) patients, high anterior rectal resection in 13/66 (19.7%), low anterior rectal resection in 12/66 (18.2%), abdominoperineal amputation of the rectum in 7/66 (10.6%), colectomy in 2/66 (3%) and proctocolectomy in 1/66 (1.5%) patient. The median follow-up was 37.5 months (range 6 to 128). The total number of surviving patients was 60 (90.9%). Conclusion: This study showed that laparoscopic colorectal surgery has good clinical and oncological outcomes.